2016
DOI: 10.1175/jamc-d-15-0304.1
|View full text |Cite
|
Sign up to set email alerts
|

The GEWEX Water Vapor Assessment: Results from Intercomparison, Trend, and Homogeneity Analysis of Total Column Water Vapor

Abstract: The Global Energy and Water Cycle Exchanges project (GEWEX) water vapor assessment’s (G-VAP) main objective is to analyze and explain strengths and weaknesses of satellite-based data records of water vapor through intercomparisons and comparisons with ground-based data. G-VAP results from the intercomparison of six total column water vapor (TCWV) data records are presented. Prior to the intercomparison, the data records were regridded to a common regular grid of 2° × 2° longitude–latitude. All data records cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 39 publications
4
93
0
Order By: Relevance
“…The intention of this effort is to showcase differences among the data records and not to characterise uncertainties. Intercomparison results for long-term data records and for profile data records are given in Schröder et al (2016) and Schröder et al (2017a,b).…”
Section: Results From Intercomparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…The intention of this effort is to showcase differences among the data records and not to characterise uncertainties. Intercomparison results for long-term data records and for profile data records are given in Schröder et al (2016) and Schröder et al (2017a,b).…”
Section: Results From Intercomparisonmentioning
confidence: 99%
“…This approach was also applied to AMSR-E JAXA. Then, all data records are 25 arithmetically averaged onto the common grid by considering all valid observations within a grid cell (see also Schröder et al, 2016). Note that the regridding procedure impacts the data record's internal variance and characteristics of extremes.…”
Section: Processingmentioning
confidence: 99%
“…This then leads to a reduction in the magnitude of errors for humidity-sensitive variables [42]. Many comparative studies have confirmed the usefulness of reanalysis data in the examination of water vapor fields [29,43,44].…”
Section: Methodsmentioning
confidence: 92%
“…Climatologic reanalysis appears to solve this problem to some extent. Despite the fact that the models used in reanalysis studies are characterized by poor parametrization of the hydrologic cycle, although errors are reduced in the course of the development of each reanalysis, the usefulness of reanalysis data (especially ERA-Interim) has been confirmed by numerous comparative studies) [29,44,59,60] featuring analyses with less temporal resolution (averaged data) and covering larger geographic areas (e.g., studies on climate change. In addition, gridded data now yield spatial information with a resolution high enough to make spatial pattern analysis possible.…”
Section: Discussionmentioning
confidence: 99%
“…However, the spatial coverage of ARSA and GNSS stations is rather poor in some regions and the majority of the open oceans are not covered at all. As the stability can be a strong function of region (Schröder et al, 2016), future efforts are needed to assess stability globally.…”
Section: Temporal Stabilitymentioning
confidence: 99%